Kansas Takes Pride in Roadside Prairies - Ron Klataske (Symphony in the Flint Hills, 2011)
Kansas Department of Transportation and the Audubon of Kansas work together to impliment the principles of IRVM, Integrated Rodeside Vegitation Management, to improve habitats, native grass, diversity, and beauty of Kansas roadsides.
Keywords: IRVM; integrated roadside vegitation management; roadside; Audubon of Kansas; snow; fence; native; plants; grass; mowing; natural; heritage; pleasant; conservation